2019
DOI: 10.3390/ani9090676
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Prolactin as a Potential Biomarker of Stress in Castrated Male Domestic Dogs

Abstract: Simple SummaryAlthough cortisol is usually considered the main reference for the assessment of stress, in some animal species it has been shown that prolactin can be used as a biomarker of both acute and chronic stress. Behavioural parameters can also be used to assess the state of welfare and stress. This study was aimed at evaluating the possible relationship between serum prolactin, serum cortisol and behavioural signs of stress in domestic dogs. To reduce the possible influence of some factors, the study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 87 publications
0
9
0
1
Order By: Relevance
“…Behavioural analysis is widely utilised to assess stress levels of animals. Common stress behaviours of dogs suggested in several other studies are vocalisation, oral behaviour, paw lifting, body shaking, and panting, among others [52,53]. One study reported that a stress behaviour visual analog scale was useful to reflect stress levels [13], while another suggested the simple summing up of the number of each stress behaviour did not show a correlation with stress biomarkers [53].…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural analysis is widely utilised to assess stress levels of animals. Common stress behaviours of dogs suggested in several other studies are vocalisation, oral behaviour, paw lifting, body shaking, and panting, among others [52,53]. One study reported that a stress behaviour visual analog scale was useful to reflect stress levels [13], while another suggested the simple summing up of the number of each stress behaviour did not show a correlation with stress biomarkers [53].…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol and corticosterone are the main stress hormones used to assess the level of stress in animals. However, according to some studies [42,43], prolactin can also be used as a biomarker of acute and chronic stress in fish, cattle, sheep, donkeys, rats, dogs, and humans. It is released from the pituitary gland in response to eating, mating, and other stimuli.…”
Section: Other Biomarkers Of Stressmentioning
confidence: 99%
“…Previous studies have indicated the interest in evaluating serum PRL in anxious dogs [19]. On the contrary, recent studies [20] highlighted that in sheltered castrated male dogs' PRL concentrations correlate neither to stress scores nor to fear behaviors, and that a weak negative correlation between cortisol and prolactin levels was possible. In previous research, we found that AD presented higher levels of blood PRL than a pet dog population in a controlled situation [11,21], emphasizing the interest of further investigating this neuromodulator.…”
Section: Introductionmentioning
confidence: 99%